IMPLEMENTASI SUPERVISE AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Trisna; Ramadhan, Fitriyadi Ramadhan; Metroyadi; Sakka, Ambo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the suboptimal implementation of academic supervision by school principals, which affects teacher performance in the learning process at the elementary school level. The purpose of this study is to analyze the implementation of academic supervision by school principals in improving teacher performance. This research employed a quantitative approach using a survey method. Data were collected through a Likert-scale questionnaire developed based on indicators of academic supervision and teacher performance, involving 10 teachers as research subjects. Data analysis was conducted using descriptive statistics and simple linear regression. The results indicate that academic supervision is categorized as good, with an average score of 60.4, while teacher performance is also categorized as good, with an average score of 62.3. Furthermore, there is a positive relationship between academic supervision and teacher performance. These findings suggest that academic supervision carried out systematically, collaboratively, and continuously can enhance the quality of learning and teacher professionalism.